Pemantauan Virus dengan Metode PCR (Polymerase Chain Reaction) di Pantai Utara Jawa Timur [Monitoring Virus By PCR Method (Polymerase Chain Reaction) In North Coast, East Java] - Hari Suprapto; Yulia Kartika (Jurnal Ilmiah Perikanan dan Kelautan, 2012)
Abstract The disease most dangerous for the cultivation activity is virus. Viruses are organisms subseluler that contain only nucleic acid (RNA or DNA) as genetic material. Koi Herpes Virus is one type of virus that causes mortality in cultured Cyprinids. KHV disease in Indonesia started in Blitar, East Java on March 2002 because the entry of imported koi fish that carry the virus KHV, while mortality prosentase could reach 80% - 85%, which causes loss of about 5 billion rupiah. In addition of KHV, there are several types of viral diseases in shrimp is White Spot Syndrome Virus (WSSV), Taura Syndrome Virus (TSV), dan Yellow Head Virus (YHV). Disease can cause losses in farming activities, such as WSSV. WSSV is an endemic disease since 1995. disease WSSV is exotic viral disease that attacks the shrimp monodon in 1998/1999 has resulted in decreased production of very large, so the Indonesian shrimp exports down 33,000 tons. Treatment of viral diseases is difficult because the virus resistant to certain antibiotics and chemical compounds. Therefore, prevention needs to be done, one through the monitoring activities conducted on the northern coast of East Java. The method implemented is monitoring in location and identification of viruses by PCR (Polymerase Chain Reaction). Monitoring in location includes water quality measurements and sampling. Identification of virus carried by IQ 2000TM. The identification procedure includes extraction, amplification and electrophoresis. Regional monitoring conducted on the northern coast of East Java includes Gresik, Lamongan, Tuban, Bangkalan, Sampang, Pamekasan, and Sumenep. Water quality at locations quite well. Results activities of monitoring on the northern coast of East Java is disease White Spot Syndrome Virus (WSSV) was found positive in several locations: Gresik, Lamongan and Tuban, while the virus Taura Syndrome Virus (TSV) and Yellow Head Virus (YHV) was not found at all locations . In tilapia, disease Koi Herpes Virus (KHV) was found positive in Tuban.